SISTEM PENDUKUNG KEPUTUSAN GURU TERBAIK MENGGUNAKAN METODE AHP-SAW (STUDI KASUS:SMK FARMASI YPIB CIREBON) - putri pratiwi, mutiara; Sugiyanto, Sugiyanto; Santoso, Sabar (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
Selecting the best teachers is crucial for maintaining the quality of education in every educational institution. High-quality teachers not only master the teaching material but also possess strong interpersonal skills and high dedication. SMK Farmasi YPIB Cirebon, located in Cirebon Regency, faces challenges in manually assessing teacher performance, which is time-consuming and prone to data loss. To address this issue, a Decision Support System (DSS) was developed using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods. AHP helps prioritize structured criteria, while SAW simplifies the evaluation calculations by assigning weights to each criterion. The four criteria used in this system are Attendance, Discipline, Responsibility, and Education Level. The implementation of this DSS is expected to improve efficiency and accuracy in the selection process of the best teachers at SMK Farmasi YPIB Cirebon. Keywords: Selection of the best teachers, Decision Support System, AHP, SAW